Penerapan Mekanisme Gugatan Sederhana dalam Sengketa Wanprestasi Akad Murabahah: Studi Putusan PA Magetan Nomor 15/Pdt.GS/2024/PA.MGT - Khairul Fadli Rambe; Lilis Afifa Zahra; Putri Melissa (Jurnal Dialektika Hukum, 2026)
The application of the simplified litigation mechanism in Islamic economic disputes is a crucial issue that tests the balance between procedural efficiency and adherence to Sharia principles. The Indonesian judiciary strives to achieve a judicial system that is simple, swift, and cost-effective, which is realized through the simplified litigation mechanism. However, Islamic economic disputes require unique legal considerations, namely the integration of positive law (PERMA) with Islamic Sharia values. This study aims to analyze the implementation, evidentiary process, and judicial reasoning in the Magetan Sharia Court Decision No. 15/Pdt.GS/2024/PA.MGT. The research design employed was a normative legal study using a single-case study approach. Data were collected through a review of primary court decisions and analyzed qualitatively and normatively using legal interpretation. The findings indicate that the GS mechanism is effectively applied in murabahah disputes, where the evidentiary process is simple and expeditious. The judge’s reasoning demonstrates a balance between positive law and the principle of al-wafa bil ‘uqud, and even rejects claims for damages deemed excessive. In conclusion, this ruling serves as an important precedent demonstrating that religious courts can function as an efficient dispute resolution forum that upholds Sharia integrity, and it is recommended for further comparative study regarding various other types of Sharia contracts.